Pengaruh Iklim Organisasi Dan Komitmen Organisasi Terhadap Organizational Citizenship Behavior Pada Karyawan Di PT Kantor Pos Indonesia - Zaki Rahadian; Sungkono (CV. ITTC INDONESIA, 2024)
The purpose of this research is to: (1) identify the influence of Organizational Citizenship Behavior and Commitment to Organizational Citizenship at the Post Office; (2) identify the simultaneous impact of Organizational Citizenship Behavior and Commitment to Organizational Citizenship at PT Kanpos Indonesia Bandung; and (3) identify the factors that most significantly influence Organizational Citizenship Behavior and Organizational Citizenship Commitment at PT. Pos Indonesia Bandung. This research uses quantitative data types and multiple linear regression analysis methods, therefore the research data comes from an online questionnaire sent to employees of PT Kantor Pos Indonesia Bandung, with a sample size of around 80 respondents. Based on the results of research using the t test and f test, it can be concluded that the research results show that work discipline has a statistically significant influence. Furthermore, it is shown that organizational citizenship behavior among employees is positively influenced by organizational culture and organizational commitment.